Effects of a virtual reality exergame on cardiorespiratory function in older adults - Dina Fatiyah Bakri; Melda Warliani; Yose Waluyo; Husnul Mubarak; Nilla Mayasari; Andi Alfian Zainuddin (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Introduction: With increasing life expectancy, the elderly population is at higher risk for cardiorespiratory decline. Exercise is known to reduce this decline, but adherence to exercise programs can be low. Virtual reality (VR) exergaming offers an engaging alternative, potentially increasing motivation while providing similar benefits. This study aimed to evaluate the effectiveness of VR exergaming in improving cardiorespiratory function in elderly individuals. Methods: A randomized controlled trial was conducted with 40 elderly participants (VR exergaming, n=24; conventional aerobic exercise, n=16). Both groups exercised three times per week for six weeks. The VR group used Ring Fit Adventure on the Nintendo Switch, while the control group performed structured aerobic exercises. Cardiorespiratory parameters—heart rate (HR), respiratory rate (RR), blood pressure (BP), predicted maximal oxygen uptake (VO₂ max) from the 6-minute walking test (6MWT), peak expiratory flow rate (PEFR), and peak cough flow rate (PCFR)—were assessed before and after the intervention. Results: Significant improvements were observed in VO₂ max, RR, BP, PEFR, and PCFR in both groups, though HR did not change significantly. Despite baseline differences in VO₂ max, overall improvements were comparable between the two groups. Conclusion: VR exergaming was as effective as conventional exercise in improving cardiorespiratory function in older adults and offers an engaging and enjoyable alternative.